Հայոց ցեղասպանությունը որպես «Հումանիզմի ճգնաժամի» դրսևորում Գոնսալո Գուարչի վեպերում - Սիրանուշ Կարապետյան (ՀՀ ԳԱԱ հրատ.)
Статья посвящена анализу романов каталонского писателя Гонсало Гуарча “Армянское древо”, “Армянское завещание” и “Белая гора”, в которых автор обратился к теме армянского геноцида. В трилогии геноцид рассматривается не только как всечеловеческая проблема, но и как спад общих нравственных норм начала 20-ого века. This article is dedicated to the study of the three novels by the Catalonian writer Gonzalo Guarch: "The Armenian Family Tree", "The Armenian heritage" and "The White Mountain". The trilogy pertains to the Armenian genocide, which is viewed not only as an all-inclusive problem of humanity but also as a manifestation of the decadence of general moral values, common to the beginning of the 20th century.
Keywords: Armenian Genocide (1915)